Agrarian India between the world wars - "Ulyanovsky, Rostislav" (Mascow, 1981)
This book by well-known Soviet Oriental expert Prof. Rostislav A. Ulyanovsky studies the evolution of the Indian countryside from the time when India was seized by the British to the eve of the Second World War. The author, who worked on his manuscript for almost 15 years, has made interesting generalisations and drawn interesting conclusion, their significance going far beyond the bounds of India only. On the basis of research into official material of the Royal Commission on Agriculture in India and the Banking Enquiry Committee for the Central Administrated Areas, which fills dozens of volumes, thousands of personal evidences, and a multitude of Soviet and other sources, the author formulates the concept of the colonial-feudal development course of Indian capitalism, burdened by a predominance of feudal survivals that were used by British capital for its own selfish purposes.
Keywords: Agricultural India